Assessment of human-induced evapotranspiration with GRACE satellites in the Ziya-Daqing Basins, China. Issue 15 (17th November 2020) - Liu, Yi; Mo, Xingguo; Hu, Shi; Chen, Xuejuan; Liu, Suxia
ABSTRACT: With the developments of population and economy, it is necessary to assess the increasing impacts of human activities on evapotranspiration (ET) for sustainable water resources management. The discrepancies between the GRACE-based ET (ETGRACE ) by water balance method and the simulated ET (ETVIP ) using VIP-RS (Remote Sensing based Vegetation Interface Processes) model were applied to quantify the human-induced ET (HET) in the Ziya-Daqing Basins (ZDB) and Gangnan Reservoir Basin (GRB) in the period 2006–2015. It was found that uncertainty of ETGRACE mainly came from terrestrial water storage changes; ETVIP was noticeably lower than ETGRACE by 13.5% and 18.5% in the ZDB and GRB, respectively; and HET had increased significantly in September, since 2013 and 2014 in the ZDB and GRB, respectively. The increase of HET in the ZDB was attributed to the increases in Gross Domestic Product (GDP) and domestic water consumption, while that in the GRB was caused by the increases in groundwater resources.